2021
DOI: 10.3390/ijerph182212162
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness: An Immunometabolic Syndrome

Abstract: Loneliness has been defined as an agonizing encounter, experienced when the need for human intimacy is not met adequately, or when a person’s social network does not match their preference, either in number or attributes. This definition helps us realize that the cause of loneliness is not merely being alone, but rather not being in the company we desire. With loneliness being introduced as a measurable, distinct psychological experience, it has been found to be associated with poor health behaviors, heightene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 184 publications
(298 reference statements)
0
21
0
Order By: Relevance
“…However, in all three studies the associations are fully explained or mediated by behavioral lifestyle factors. Social isolation and loneliness are also associated with immune system and endocrine issues [18 ▪ ,28 ▪ ]. Further social isolation and loneliness are related to a range of poor mental health outcomes, most commonly depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in all three studies the associations are fully explained or mediated by behavioral lifestyle factors. Social isolation and loneliness are also associated with immune system and endocrine issues [18 ▪ ,28 ▪ ]. Further social isolation and loneliness are related to a range of poor mental health outcomes, most commonly depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pourriyahi and colleagues [28 ▪ ] proposed that loneliness is an immunometabolism syndrome. Evidence has demonstrated that loneliness is associated with poor health behaviors, a heightened stress response and a reduction in the body's ability for physiological restoration [28 ▪ ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same systematic review documented a relationship between loneliness and increased risk for the onset of dementia, as well as an increase in biological markers (amyloid and tau burden) associated with Alzheimer’s disease. Furthermore, loneliness is related to various metabolic alterations, such as type 2 diabetes mellitus, dyslipidemia, metabolic syndrome, hypertension, and other cardiovascular risk markers [ 114 ].…”
Section: Mental States and Molecular Biologymentioning
confidence: 99%
“…These variances not only depend on how the personality characteristics of habits were constructed, but also on the state in which the individual was in the initial stage of measurement and data collection. In addition, Pourriyahi et al (2021) report in their research a series of neuroimmunoendocrine changes in the different ways in which we socialize andmainly -we do not socialize, which are managed in a way by the psychosocial environment around the individual and activate triggers that behave as stressors. Ponomarev et al (2021), in turn, in their research, observe the immune system in controlled environments and report the difficulty of accuracy in the data due to the colossal variance of the results, as these are a consequence of the relationship between the neurological, endocrine and immune systems.…”
Section: Collected Datamentioning
confidence: 99%